Capital Commitment and Illiquidity in Corporate Bonds. (12th July 2018) - BESSEMBINDER, HENDRIK; JACOBSEN, STACEY; MAXWELL, WILLIAM; VENKATARAMAN, KUMAR
ABSTRACT: We study trading costs and dealer behavior in U.S. corporate bond markets from 2006 to 2016. Despite a temporary spike during the financial crisis, average trade execution costs have not increased notably over time. However, dealer capital commitment, turnover, block trade frequency, and average trade size decreased during the financial crisis and thereafter. These declines are attributable to bank‐affiliated dealers, as nonbank dealers have increased their market commitment. Our evidence indicates that liquidity provision in the corporate bond markets is evolving away from the commitment of bank‐affiliated dealer capital to absorb customer imbalances, and that postcrisis banking regulations likely contribute.